Development of ABS based wire as feedstock filament of FDM for industrial applications. Issue 2 (21st March 2016) - Singh, Rupinder; Singh, Sunpreet; Mankotia, Karan
Abstract : Purpose: Acrylonitrile-butadiene-styrene (ABS)-based plastic is one of the most widely used filament materials for fused deposition modelling (FDM) applications. Because the FDM system, as well as its filament material (ABS), has been patented by commercial manufacturers, the cost of the filament material is significantly high, which affects the commercialization of this technology for medium- and small-scale industries. This problem may be addressed by developing alternative FDM filament material at the user end. The present research work aims to make an effort to develop cost-effective ABS filament with acceptable mechanical properties at par with the filament prepared by commercial manufacturers. Further, mathematical models have been developed for optimizing mechanical properties (like: tensile strength, Young's modulus and dimensional accuracy) of in-house-fabricated filament. Design/methodology/approach: The processing parameters (such as barrel temperature, screw speed and take-up speed) of single-screw extruder used to fabricate ABS filament have been studied and optimized. Findings: Although the mechanical properties of fabricated ABS filament were not better than those of the original equipment manufacturer (OEM) filament, yet significant cost reduction was achieved with in-house fabrication. Mechanical properties like tensile strength, Young's modulus and dimensional accuracy have been optimized using response surface methodology (RSM) for acceptability of in-house-fabricated filament (for commercial applications) at par with the OEM filament. Originality/value: This paper highlights the systematic steps for in-house fabrication of cost-effective FDM filament. Further, RSM-based mathematical models have been developed for optimizing mechanical properties of newly fabricated filament.